Elective practical training in the nursing student formation: some reflexions - Cibele Almeida Torres; Maria Grasiela Teixeira Barroso (Rev Rene)
The present study aims to refl ect on a nursing student’s experience in the elective practical training in a public hospital in Fortaleza, Ceará. It is a descriptive and exploratory study,developed from February to March 2007, using the participant observation and fi eldwork diary. This study makes connections between students’ experience and pertinent literature. It was structured in two parts: considerations about the hospital environment and the insertion of the student in this environment.It refl ected on the Nursing assistance, health-disease process, humanization, health promotion, interdisciplinarity and integrality. It shows positive points on the perspective of the improvement of theoretical-practical abilities. The points to be improved are related to the knowledge defi cit as well as the diffi culty to accomplish an interdisciplinary and humanized practice. Therefore, it is understood to be indispensable for the university to appropriate constructive criticism. It can lead the student to an educational improvement, from the standpoint of college students, teachers and professionals